2017
DOI: 10.1364/oe.25.021711
|View full text |Cite|
|
Sign up to set email alerts
|

Sensitive and broadband measurement of dispersion in a cavity using a Fourier transform spectrometer with kHz resolution

Abstract: Optical cavities provide high sensitivity to dispersion since their resonance frequencies depend on the index of refraction. We present a direct, broadband, and accurate measurement of the modes of a high finesse cavity using an optical frequency comb and a mechanical Fourier transform spectrometer with a kHz-level resolution. We characterize 16000 cavity modes spanning 16 THz of bandwidth in terms of center frequency, linewidth, and amplitude. We retrieve the group delay dispersion of the cavity mirror coatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 25 publications
(38 reference statements)
0
26
0
Order By: Relevance
“…If needed, spectral features narrower than f rep can be measured with no ILS distortion using the method of comb-based FTS with sub-nominal resolution, in which interferograms with length matched precisely to c/f rep are measured. 23,28,29 The detection limit of OFC-PAS can be improved by several measures. First of all, a factor of 40 improvement can be expected using available high-power mid-IR OFC sources 30 with an output power of up to 1.5 W, compared to 36 mW of the signal comb used in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If needed, spectral features narrower than f rep can be measured with no ILS distortion using the method of comb-based FTS with sub-nominal resolution, in which interferograms with length matched precisely to c/f rep are measured. 23,28,29 The detection limit of OFC-PAS can be improved by several measures. First of all, a factor of 40 improvement can be expected using available high-power mid-IR OFC sources 30 with an output power of up to 1.5 W, compared to 36 mW of the signal comb used in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Using an optical frequency comb (OFC) as a light source for Fourier transform spectrometers (FTS), in the so-called combbased FTS, allows much faster acquisition (of the order of seconds) of spectra with high signal-to-noise ratio (S/N), 22 and resolution down to kHz range with no ILS contribution. 23 Here, we report the first demonstration of photoacoustic spectroscopy using an optical frequency comb. We call the technique: optical frequency comb photoacoustic spectroscopy (OFC-PAS).…”
Section: Introductionmentioning
confidence: 93%
“…With high acquisition rates (up to 2 × 1/Δ rep ) and a highthroughput data stream amenable to actively controlled coherent averaging [60], postprocessing [57], and/or adaptive sampling [58], deep averaging of fitted spectroscopic parameters is possible, and therefore so is high precision. Although intensity measurements of cavity transmission modes can also measure complex molecular response (via mode position and line width) [92][93][94][95], those techniques each require laser scanning, and therefore are inherently…”
Section: Discussionmentioning
confidence: 99%
“…1, follows in large the one used in ref. [19]. The resonances of a Fabry-Perot cavity are probed by an Er:fiber frequency comb, and the light transmitted through the cavity is analyzed with a fast-scanning Fourier transform spectrometer (FTS) with sub-nominal resolution [18].…”
Section: Methodsmentioning
confidence: 99%
“…A Lorentzian function is fitted to each cavity mode to retrieve its center frequency, width, and amplitude. We have previously demonstrated that cavity mode frequencies can be used for highprecision retrieval of broadband intracavity group delay dispersion [19]. Here we utilize the full potential of cavity mode characterization and retrieve dispersion and absorption spectra of three combination bands of CO 2 from the cavity mode shifts and broadenings, as well as the corresponding cavity-enhanced transmission spectra from the cavity mode amplitudes.…”
Section: Introductionmentioning
confidence: 99%